Explorative Investigation into the Drivers of Firm Failure - Loong, James Seng Wai (2007)
A simple fact of life is that firms fail everyday. Although some sporadic literature exists that begins to delve into the subject, there is very little current research dedicated to finding out how and why these organisations are failing and almost no research conducted about the potential remedies that would prevent them from doing so in future. What is known about firm failure indicates that the drivers of failure are not necessarily the opposites of the drivers for success, but what is not known about failure is immense.